Pulmonary arterial hypertension associated with protein kinase inhibitors: a pharmacovigilance–pharmacodynamic study. Issue 5 (9th May 2019) - Cornet, Lucie; Khouri, Charles; Roustit, Matthieu; Guignabert, Christophe; Chaumais, Marie-Camille; Humbert, Marc; Revol, Bruno; Despas, Fabien; Montani, David; Cracowski, Jean-Luc
The pathophysiology of pulmonary arterial hypertension (PAH) induced by protein kinase inhibitors (PKIs) remains unclear. To gain knowledge into this rare and severe pathology we performed a study combining a pharmacovigilance approach and the pharmacodynamic properties of PKIs. A disproportionality analysis on the World Health Organization pharmacovigilance database VigiBase using the reporting odds ratio (ROR) and 95% confidence interval was first performed. Then, we identified the most relevant cellular targets of interest through a systematic literature review and correlated the pharmacovigilance signals with the affinity for the different PKIs. We further performed a hierarchical cluster analysis to assess patterns of binding affinity. A positive disproportionality signal was found for dasatinib, bosutinib, ponatinib, ruxolitinib and nilotinib. Five non-receptor protein kinases significantly correlate with disproportionality signals: c-Src (r=0.79, p=0.00027), c-Yes (r=0.82, p=0.00015), Lck (r=0.81, p=0.00046) and Lyn (r=0.80, p=0.00036), all belonging to the Src protein kinase family, and TEC (r=0.85, p=0.00006). Kinases of the bone morphogenetic protein signalling pathway also seem to play a role in the pathophysiology of PKI-induced PAH. Interestingly, the dasatinib affinity profile seems to be different from that of other PKIs in the cluster analysis. The study highlights the potential role of the Src protein kinase family and TEC in PAH induced by PKIs. This approach combining pharmacovigilance and pharmacodynamics data allowed us to generate some hypotheses about the pathophysiology of the disease; however, the results have to be confirmed by further studies. Using the WHO pharmacovigilance database, PAH was found to be associated with dasatinib, bosutinib, ponatinib, ruxolitinib and nilotinib. The potential role of Src protein kinases and TEC in PAH induced by protein kinase inhibitors is further highlighted. http://ow.ly/56sO30nMKMj